Remote work and social jetlag: Systematic review and empirical investigation of the healthy adult working force in Finland - Peltoniemi, Jouni (My University, 2023)
This study aimed to investigate the association between remote work and sleep parameters (social jetlag, self-reported sleep quality, and sleep duration) among healthy adult working force in Finland. The hypothesis was that remote work would reduce social obligations, which are the main cause of social jetlag, and therefore associate with smaller amount of social jetlag and with other sleep parameters, especially among evening chronotypes. This hypothesis was based on a systematic review of effects of COVID-19 restrictions on social jetlag, which was conducted. This thesis utilizes data from a survey conducted in Climate Nudge Project and included 830 participants who worked or studied full-time after excluding those with sleep, health, or work ability issues. Remote work was operationalized as work modality and as frequency of work at the workplace. Statistical analyses were conducted using t-tests for work modality and simple linear regression and general linear models to assess the association between remote work and sleep parameters after inclusion of covariates. Remote work was associated with longer sleep duration and smaller amount of social jetlag. Those with any amount of remote work (work modality) compared with full week of work at the workplace had 17 minutes longer sleep duration during weekdays and 21 minutes shorter social jetlag. Predictions from general linear model produced similar results and these associations were strongest among evening types. Overall, these findings suggest that remote work may have a beneficial impact on sleep duration and social jetlag. Future studies should examine whether remote work increases productivity, which could increase the opportunities for remote work within companies and therefore utilize the beneficial association between remote work and sleep.

Tämä tutkimus tutki etätyön ja uniparametrien (sosiaalinen aikaerorasitus, itsearvioitu unen laatu ja unen kesto) välistä yhteyttä suomalaisessa terveessä aikuisväestössä. Tutkimuksen hypoteesi oli, että etätyö vähentäisi sosiaalisten velvollisuuksien määrää, jotka ovat sosiaalisen aikaerorasituksen pääaiheuttajia, mikä olisi yhteydessä alhaisempaan sosiaaliseen aikaerorasitukseen sekä muihin uniparametreihin, erityisesti iltatyypeillä. Tutkimuksen hypoteesi perustui tehtyyn systemaattiseen katsaukseen COVID-19 rajoitusten vaikutuksista sosiaaliseen aikaerorasitukseen. Tämä pro gradu -tutkielma hyödyntää kyselydataa Ilmastotuuppaus-projektista. Tutkimus sisälsi 830 vastaajaa, jotka työskentelivät tai opiskelivat täysipäiväisesti ilman unen, terveyden tai työkyvyn ongelmia Etätyö operationalisoitiin työmuotona sekä työpaikalla tehdyn työn frekvenssinä. Tilastolliset analyysit suoritettiin käyttämällä t-testejä työmuodolle sekä yksinkertaisia lineaarisia regressio- ja yleisiä lineaarisia malleja arvioimaan etätyön ja uniparametrien välistä yhteyttä kovariaattien huomioimisen jälkeen. Etätyö oli yhteydessä pidempään unen kestoon sekä vähäisempään sosiaaliseen aikaerorasitukseen. Mikä tahansa määrä etätyötä (työmuoto) verrattuna koko viikon työhön työpaikalla, oli yhteydessä 17 minuuttia pidempään unen kestoon ja 21 minuuttia lyhyempään sosiaaliseen aikaerorasitukseen. Yleisen lineaarisen mallin mallinnukset antoivat vastaavanlaiset tulokset ja nämä yhteydet olivat suurimpia iltatyypeillä. Kaikkiaan, nämä tulokset antavat viitteitä, että etätyöllä voi olla positiivisen yhteys unen kestoon ja sosiaaliseen aikaerorasitukseen. Jatkotutkimusten tulisi tutkia lisääkö etätyö työn tuottavuutta, mikä voisi olla tapa lisätä etätyön mahdollisuutta yrityksissä ja sitä kautta hyödyntää etätyön hyödyllistä vaikutusta uneen.
Keywords: Adult, Chronotype, COVID-19, Distance work, Systematic review, Sleep deprivation, Sleep duration, Sleep quality, Sleep-wake timing